2020
DOI: 10.1249/mss.0000000000002306
|View full text |Cite
|
Sign up to set email alerts
|

Posture and Physical Activity Detection: Impact of Number of Sensors and Feature Type

Abstract: Studies using wearable sensors to measure posture, physical activity (PA), and sedentary behavior typically use a single sensor worn on the ankle, thigh, wrist, or hip. Although the use of single sensors may be convenient, using multiple sensors is becoming more practical as sensors miniaturize. Purpose We evaluated the effect of single-site versus multisite motion sensing at seven body locations (both ankles, wrists, hips, and dominant thigh) on the detection of physical beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…For a binary classification task, Figure 3 shows a framework diagram of the confusion matrix. TP refers to true example, FP refers to false positive example, TN refers to true negative example, and FN refers to false negative example; F1-score represents the harmonic average of precision and recall [17]. It is one of the main indexes for model evaluation with specificity.…”
Section: Experimental Model Performance Indicatorsmentioning
confidence: 99%
“…For a binary classification task, Figure 3 shows a framework diagram of the confusion matrix. TP refers to true example, FP refers to false positive example, TN refers to true negative example, and FN refers to false negative example; F1-score represents the harmonic average of precision and recall [17]. It is one of the main indexes for model evaluation with specificity.…”
Section: Experimental Model Performance Indicatorsmentioning
confidence: 99%
“…When an accelerometer is placed on a body location that moves into a fixed anatomical plane in different postures, the changes in accelerometer orientation from tilt angle can be used to detect the posture with a high accuracy. Skotte et al [44] and Edwardson et al [45] have previously demonstrated that thigh-worn classifiers can differentiate sitting and standing, whereas Gjoreski et al [46], Tang et al [47], and Narayanan et al [48] have shown that a two-placement combination of the thigh and hip/back results in an excellent recognition of lying, sitting, and standing. Prior studies have also demonstrated that thigh-worn monitors, such as activPAL and Uptimer, provide acceptable estimates of sitting and standing among children with CP who have mild motor impairments [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…These devices will be worn on the non-dominant wrist. Wrist sensor data will be processed using Monitor-Independent Movement Summary unit (MIMS) to yield overall movement volume estimations [ 40 ] and machine learning algorithms to yield sensor wear, sleep, and wake behavior characterization (i.e., sedentary, ambulation, and upright behaviors) [ 41 , 42 , 43 , 44 ] during the 16-week intervention period. (ii) Health outcomes : (a) anthropometrics (height, weight, and waist/hip circumference); (b) body composition (via bioelectrical impedance) [ 45 ]; (c) seated resting heart rate and blood pressure; (d) fasting blood biomarkers (blood glucose and lipid profile); (e) cognition (via The NIH Toolbox Cognition Battery) [ 46 ]; (f) physical function (via The Short Physical Performance Battery) [ 47 , 48 ]; (g) upper and lower body muscle endurance (via maximal push-up and squat tests, respectively) [ 49 ]; (h) aerobic fitness (via the six-minute walk test) [ 50 , 51 ]; and (i) other questionnaire-based health outcomes (see supplementary study protocol ).…”
Section: Methodsmentioning
confidence: 99%